Fraternity as Natural Being - Joachim Ostermann (Religions, 2022)
In a scientifically understood world, making sense of natural being is a challenge. This is particularly acute when knowledge of nature impinges on human autonomy. I present two examples: The legitimacy of opposing abortion on account of “potential life”, and the legitimacy of mandatory vaccination during a pandemic. I then explore the concept of fraternity in the writings of St. Francis at the example of the Rule of 1221 and the Canticle of Creatures. In conclusion, I show how the concept of fraternity as applied in Franciscan life allows us to reconcile the relationship between natural being and human autonomy through relationships of mutual care.